State influence on the socio-environmental conflict surrounding palm oil in Colombia - Marlés Herrera, María Susana; Mendoza Chacón, Wilkar Simón; Caballero Velasco, Daniel Felipe (Revista del CLAD Reforma y Democracia, 2025)
The oil palm is an important productive engine in rural territory whose extractivist logic envisions risks to the environment and society. This research sought to analyze the role of the State in the development of the palm oil agroindustry in Colombia from 1945 to 2022, under a descriptive methodology with documentary, evolutionary and multivariable design. A historical difference was found in the palm border, noting the significant expansion after including the palm business in the public agenda, in parallel, impacts have been recorded against the environment and the peasant and ethnic communities, whose echo in history remains, in addition, the analysis of the legal-administrative framework regarding palm oil reflects a weak sustainable development model, based on anthropocentrism. This background reveals the fallacious discourse about the Ecological Constitution and a strong challenge that the subsequent governments must deal with, since the country requires measures to promote the financial sustainability of the rural area with respect for socio-environmental integrity.
Keywords: agroindustry; sustainable development; environmental impact; social impact; public policies